2018
DOI: 10.1177/2333721418778195
|View full text |Cite
|
Sign up to set email alerts
|

What Matters Most at the End-of-Life for Chinese Americans?

Abstract: Background: To provide optimal end-of-life (EOL) care in the Chinese American population, we need to have a better understanding of what matters most at EOL from their perspective. Experiencing a “good death” at the EOL is the optimal goal of palliative care. Studies show that the meaning and description of good death varies across cultures in different populations. In the United States, Chinese Americans comprise the largest Asian demographic. Aim: To describe EOL wishes, which define a good death for Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…While the GoWish cards have been used in several recent studies of different contexts and populations ( Banner et al, 2019 ; Delgado-Guay et al, 2016 ; Glennon et al, 2019 ; Kuramoto et al, 2015 ; Zachariah, Klein, Clifton-Hawkins, Andrews, & Gross, 2015 ), we have found few other studies reporting on how GoWish items have been reasoned about and negotiated by users. The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items. While reasoning and prioritizations of the card item “Not being a burden to my family/those close to me” seem similar in both studies, consideration of the card item “Being free of pain” has notable differences, as the study by Lee and colleagues (2018) reports only on reasoning about the physical experience of pain, whereas we have found different underlying ways of reasoning for prioritizing this and other card items among different individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the GoWish cards have been used in several recent studies of different contexts and populations ( Banner et al, 2019 ; Delgado-Guay et al, 2016 ; Glennon et al, 2019 ; Kuramoto et al, 2015 ; Zachariah, Klein, Clifton-Hawkins, Andrews, & Gross, 2015 ), we have found few other studies reporting on how GoWish items have been reasoned about and negotiated by users. The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items. While reasoning and prioritizations of the card item “Not being a burden to my family/those close to me” seem similar in both studies, consideration of the card item “Being free of pain” has notable differences, as the study by Lee and colleagues (2018) reports only on reasoning about the physical experience of pain, whereas we have found different underlying ways of reasoning for prioritizing this and other card items among different individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items. While reasoning and prioritizations of the card item “Not being a burden to my family/those close to me” seem similar in both studies, consideration of the card item “Being free of pain” has notable differences, as the study by Lee and colleagues (2018) reports only on reasoning about the physical experience of pain, whereas we have found different underlying ways of reasoning for prioritizing this and other card items among different individuals. Furthermore, as no wild cards were used in the study by Lee and colleagues (2018) , and are rarely reported in other studies ( Lankarani-Fard et al, 2010 ; Litzelman et al, 2017 ), our in-depth descriptions of how participants have reasoned when considering the wild cards are of value for understanding the very individual nature of prioritization of EoL preferences.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to quality of life in older age, Tang, Chen, Zhang, and Mui (2018) found that employment status and urban versus rural locations are related to life satisfaction among Chinese older adults in China. Regarding the role of traditional cultural values, Zhang, Liu, and Wu (2018) observed traditional familism values and practice as key determinants of successful aging among Chinese in Hawai’i, which were additionally noted by Lee, Hinderer, and Alexander (2018) in discussing end-of-life care among Chinese Americans. Together, these articles highlight the need for the development of intervention strategies for U.S. Chinese communities through a culturally appropriate design.…”
Section: Study Findingsmentioning
confidence: 95%
“…In addition, "In traditional Chinese culture, the concepts of living in a nursing home away from family, or needing to be "cleaned up" by others who are not family members are examples of losing dignity for the individual and not fulfilling Xiao [filial piety] by their children." [29] Among the physical needs at EOL, being pain-free was the top element of a good death in the population studied by Lee et al This study also found that "Prayer and spirituality were seen as essential to a good death in Chinese Americans", and that "patients at EOL found peace and comfort through prayer." Another psychosocial need considered part of "a good death" included having family members present to create a sense of security and comfort.…”
Section: Racial and Ethno-cultural Issues In Palliative And End-of-limentioning
confidence: 85%
“…[Furthermore+, in managing EOL care of parents, a good and "filial" child is expected to do everything to prolong their parents' life." [29] This expectation has generated ethical conflicts between the ethical principles of truth-telling and informed consent that govern modern Western medical ethics and the duties of filial piety so important in Chinese society. [30] It is crucial for health care professionals to balance these considerations through ensuring that the individual patient wishes to defer discussions and decisions at the end-of-life to their adult children.…”
Section: Racial and Ethno-cultural Issues In Palliative And End-of-limentioning
confidence: 99%